Self-efficacy of people who are at risk of tuberculosis in the work area of the garuda public health center in Bandung - Hadiyani, Wini; Muhamad Dony Faturrahman; Rizal Ilbert (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims : This study aims to determine self-efficacy in individuals who are at risk for tuberculosis. Design : This study used a descriptive method and was conducted in August 2019 with 119 respondents who were sellected by using random s The number of samples is 119 respondents with inclusion criteria: respondents in their area there are TB cases, aged 18-45 years, can read and write, and do not have hearing or vision impairments. Exclusion criteria: have a mental disorder. Sampling was obtained through random sampling. Methdos : This research is a quantitative descriptive research. Results : this study has shown that more than half of the respondents have low self-efficacy as many as 63 people (52.9%). Conclusions : self-efficacy in individuals who are at risk for tuberculosis is still low. The lack of knowledge that contributes to the prevention of tuberculosis is still a problem. Support from the environment and the closest people is needed so that family empowerment can increase self-efficacy